Usulan Desain Troli Barang Menggunakan Pendekatan Antropometri Dan Ergonomi Partisipatori (Studi Kasus PT. Mataram Tunggal Garment) - Mukhamad Nur Iskandar; Dian Janari (Industry Xplore, 2021)
Material handling is very important in the production process. PT. Mataram Tunggal Garment uses a goods trolley as a tool to mobilize cardboard boxes containing products. In practice, many employees experience complaints such as back pain due to manually raising and lowering product, difficulty passing downhill and incline due to the absence of brakes, the trolley is difficult to operate, and the trolley is too heavy. If this problem is not resolved immediately, it will have a negative impact on employee safety and company productivity. Therefore, this study aims to design recommendations for goods trolley in the finishing and packing division. From the results, the percentile used for shoulder width is P95: 53 cm, standing elbow height is P5: 84.5 cm and forward hand reach is P5: 65 cm. The proposed design is to add brakes to make it easier to go through inclines or descents, the handle of the trolley can be adjusted in height, the trolley is designed to raise and lower cartons automatically, the size of the trolley container is made to be adjusted to the size of the carton, adding wheel locks, and choosing the stainless steel and polypropylene plastic as a material because of their strength and lightness.